2012
DOI: 10.3109/09553002.2012.683511
|View full text |Cite
|
Sign up to set email alerts
|

Induction of lethal bystander effects in human breast cancer cell cultures by DNA-incorporated Iodine-125 depends on phenotype

Abstract: Purpose This study uses a three-dimensional cell culture model to investigate lethal bystander effects in human breast cancer cell cultures (MCF-7, MDA-MB-231) treated with 125I-labeled 5-iodo-2′-deoxyuridine (125IdU). These breast cancer cell lines respectively form metastatic xenografts in nude mice in an estrogen-dependent and independent manner. Materials and methods In the present study, these cells were cultured in loosely-packed three-dimensional architecture in a Cytomatrix™ carbon scaffold. Cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…In contrast, other studies with human cells exposed to low doses of sparsely ionizing radiations suggested that junctional communication enhances the expression of protective effects against clastogenic and lethal damages [23, 24]. Together, the studies support the concept that the nature of the effects of junctional communication in response to irradiation or other toxic agents greatly depend on the type and dose of the stressful agent, the biochemical change produced in the targeted cells and the genotype and/or phenotype of the targeted and bystander cells [5, 25, 26]. Depending on connexin, gap junction channels mediate the propagation of biochemical signals that either enhance or mitigate stressful effects in targeted cells, and in some cases result in important biological changes in non-targeted cells in the vicinity that can persist over multiple cellular divisions (reviewed in [27, 28]).…”
Section: Introductionmentioning
confidence: 81%
“…In contrast, other studies with human cells exposed to low doses of sparsely ionizing radiations suggested that junctional communication enhances the expression of protective effects against clastogenic and lethal damages [23, 24]. Together, the studies support the concept that the nature of the effects of junctional communication in response to irradiation or other toxic agents greatly depend on the type and dose of the stressful agent, the biochemical change produced in the targeted cells and the genotype and/or phenotype of the targeted and bystander cells [5, 25, 26]. Depending on connexin, gap junction channels mediate the propagation of biochemical signals that either enhance or mitigate stressful effects in targeted cells, and in some cases result in important biological changes in non-targeted cells in the vicinity that can persist over multiple cellular divisions (reviewed in [27, 28]).…”
Section: Introductionmentioning
confidence: 81%
“…Inhibitory bystander effects were also observed with 125 I-UdR in vitro in chinese hamster V79 cells (85), in colon cancer cells (86) and in the breast cancer cell line MCF7 (84). However, in another breast cancer cell line (MDA-MB-231) no bystander effects were observed indicating that differences in the phenotypes of cells also could play a role in the induction of bystander effects (87). In vivo experiments using human colon carcinoma cells, labeled with a lethal dose of 125 I-UdR prior to mixing with unlabeled cells and before injection into nude mice showed a significant inhibitory effect on tumor growth due to bystander effects in the non-labeled cells (88).…”
Section: Bystander Effectsmentioning
confidence: 92%
“…However, it cannot be excluded that DNA/ 125 IUDR or other radioactive molecular products released from damaged cells can additionally target neighbor cells directly, although this possibility is not considered by authors. The secretion of radiolabeled DNA derivatives resulting from damaged cells could be probably partly responsible for the different ability of various cells to induce a bystander effect observed by Akadugu et al [59]. In the studies performed on human breast carcinoma MDA-MB-231 or MCF-7 cells using 3-D cell culture on carbon scaffold they demonstrated the capacity of 125 IUdR to induce lethal bystander effects in human breast cancer cells MCF-7 line but not in MDA-MB-231 cell line indicating that the bystander response is cell type dependent.…”
Section: In Vitro Studies Of Radionuclide Induced Bystander Effectmentioning
confidence: 99%